2001
DOI: 10.1046/j.1365-2958.2001.02204.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a lipopolysaccharide α‐2,3‐sialyltransferase from Haemophilus influenzae

Abstract: We have identified a gene for the addition of N‐acetylneuraminic acid (Neu5Ac) in an α‐2,3‐linkage to a lactosyl acceptor moiety of the lipopolysaccharide (LPS) of the human pathogen Haemophilus influenzae. The gene is one that was identified previously as a phase‐variable gene known as lic3A. Extracts of H. influenzae, as well as recombinant Escherichia coli strains producing Lic3A, demonstrate sialyltransferase activity in assays using synthetic fluorescent acceptors with a terminal galactosyl, lactosyl or N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
140
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 119 publications
(148 citation statements)
references
References 25 publications
(67 reference statements)
5
140
0
3
Order By: Relevance
“…The main sialyltransferase is Lic3A (Fig. 1), which adds a-2,3-Neu5Ac (Hood et al, 2001), and has been shown to be absolutely required for bacterial survival in the middle ear in an animal model of otitis media (Bouchet et al, 2003). Amongst the other sialyltransferases, the Lic3A-homologue Lic3B is a bifunctional enzyme that can add mono-or disialic acid to the LPS acceptor ( Fig.…”
Section: Deploying Sialic Acid Onto the Battlefieldsynthesis Of Sialimentioning
confidence: 99%
“…The main sialyltransferase is Lic3A (Fig. 1), which adds a-2,3-Neu5Ac (Hood et al, 2001), and has been shown to be absolutely required for bacterial survival in the middle ear in an animal model of otitis media (Bouchet et al, 2003). Amongst the other sialyltransferases, the Lic3A-homologue Lic3B is a bifunctional enzyme that can add mono-or disialic acid to the LPS acceptor ( Fig.…”
Section: Deploying Sialic Acid Onto the Battlefieldsynthesis Of Sialimentioning
confidence: 99%
“…The sialylation of LPS glycoforms by strain 486 depends only on the Lic3A sialyltransferase (7,17) and therefore inactivation of lic3A by insertion of a kanamycin resistance cassette (7) completely prevented expression of sialylated glycoforms. Isogenic sialic acid-deficient mutants of NTHi strains 162, 285, 375, 477, and 486 were constructed by mutating the gene encoding CMP-Neu5Ac synthetase (siaB) as described (6).…”
Section: Construction Of Mutant Strains Unable To Synthesize Sialylatmentioning
confidence: 99%
“…Isogenic sialic acid-deficient mutants of NTHi strains 162, 285, 375, 477, and 486 were constructed by mutating the gene encoding CMP-Neu5Ac synthetase (siaB) as described (6). We confirmed the genotype of all mutants by using PCR and Southern hybridization (6,7). The LPS phenotypes were confirmed as described (6).…”
Section: Construction Of Mutant Strains Unable To Synthesize Sialylatmentioning
confidence: 99%
See 1 more Smart Citation
“…Many pathogenic bacteria, such as H. influenzae, N. gonorrhoeae , and N. meningitides , can decorate their LOS by sialylation, either by incorporating Neu5Ac into their LOS, cell membrane or capsule. Alternatively, some of the Escherichia coli strains and N. meningitidis produce capsular polysaccharides containing Neu5Ac [37]. The mechanism of LOS sialylation in these microbes differs.…”
Section: Discussionmentioning
confidence: 99%